An Empirical Equilibrium Model of a Decentralized Asset Market - Gavazza, Alessandro (Econometrica, 2016)
I estimate a search-and-bargaining model of a decentralized market to quantify the effects of trading frictions on asset allocations and asset prices, and to quantify the effects of intermediaries that facilitate trade. Using business-aircraft data, I find that, relative to the Walrasian benchmark, 12 percent of the assets are misallocated, and pricesareapproximately 24.5-percent lower. Dealers play an importantroleinreducing frictions: In a market with no dealers, 15.2 percent of the assets would be misallocated. Perhaps surprisingly, in a market with no dealers, prices would increase by 1.7 percent, because sellers ’ outside options improve relative to buyers’, thus counteracting the effects of higher search costs and slower trade on asset prices.